Pengaruh Pengalaman Magang, Kemampuan Mahasiswa, dan Konteks Kerja Terhadap Keinginan Menjadi Akuntan Publik - Sophia Everly; Nuvia kurnia sari (Jurnal Bisnis Kreatif dan Inovatif, 2024)
This research aims to investigate the impact of internship experience, student abilities, and work context on students' desire to become public accountants. Internship experience is considered an important factor in shaping students' understanding and practical skills in the world of work. Students' abilities, whether acquired during formal education or through internship experience, are also thought to play a key role in determining their desire to pursue a career as a public accountant. In addition, the work context, including the organizational environment and work culture, can influence students' perceptions of the sustainability of their careers in the field of public accounting. This research method involves surveys and statistical data analysis to evaluate the relationship between internship experience, students' abilities, work context, and their desire to become public accountants.